Gas exchange at whole plant level shows that a less conservative water use is linked to a higher performance in three ecologically distinct pine species. (21st March 2018) - Salazar-Tortosa, D; Castro, J; Rubio de Casas, R; Viñegla, B; Sánchez-Cañete, E P; Villar-Salvador, P
Abstract: Increasing temperatures and decreasing precipitation in large areas of the planet as a consequence of global warming will affect plant growth and survival. However, the impact of climatic conditions will differ across species depending on their stomatal response to increasing aridity, as this will ultimately affect the balance between carbon assimilation and water loss. In this study, we monitored gas exchange, growth and survival in saplings of three widely distributed European pine species ( Pinus halepensis, P. nigra and P. sylvestris ) with contrasting distribution and ecological requirements in order to ascertain the relationship between stomatal control and plant performance. The experiment was conducted in a common garden environment resembling rainfall and temperature conditions that two of the three species are expected to encounter in the near future. In addition, gas exchange was monitored both at the leaf and at the whole-plant level using a transient-state closed chamber, which allowed us to model the response of the whole plant to increased air evaporative demand (AED). P. sylvestris was the species with lowest survival and performance. By contrast, P. halepensis showed no mortality, much higher growth (two orders of magnitude), carbon assimilation (ca. 14 fold higher) and stomatal conductance and water transpiration (ca. 4 fold higher) than the other two species. As a consequence, P. halepensis exhibited higher values of water-use efficiency than the rest of the species even at the highest values of AED. Overall, the results strongly support that the weaker stomatal control of P. halepensis, which is linked to lower stem water potential, enabled this species to maximize carbon uptake under drought stress and ultimately outperform the more water conservative P. nigra and P. sylvestris . These results suggest that under a hotter drought scenario P. nigra and P. sylvestris would very likely suffer increased mortality, whereas P. halepensis could maintain gas exchange and avoid water-induced growth limitation. This might ultimately foster an expansion of P. halepensis to higher latitudes and elevations.